Receiving Countries' Perspectives: The Case of Sweden - Christer Gerdes; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2014)
Sweden has made its labour market more open for labour immigration since the mid1990s: becoming member of the common labour market of EES/EU in 1994, no transitional rules introduced at the enlargement of European Union in 2004 and 2007, and opening up for labour migration from non-EES/EU countries in December 2008. The changes have led to increased labour immigration. The labour immigration expanded for example after the enlargement in 2004 but not so much as in for example the United Kingdom and Ireland. Other forms of immigration have been more important. On the other hand, the migration has been rather stable in the years after the crisis in 2008. The main explanation is most likely that the recession in Sweden was only for one year, 2009, and that it was concentrated to some parts of the manufacturing industry where few migrant workers were employed. If the present EMU crisis is spreading to Sweden the result may of course be different.
Keywords: F22; J15; J31; J61; 330; immigration; wages; EU enlargement; Sweden